Penerapan Pidana Tambahan Berupa Uang Pengganti Dalam Perkara Tindak Pidana Korupsi Mantan Bupati Kabupaten Kupang Ibrahim Agustinus Medah (Putusan No.78/Pid.Sus-TPK/2021/PN. KPG) - Sine, Jeremy Alexander; Manuain, Orpa Ganefo; Fanggi, Rosalind Angel (Artemis Law Journal, 2025)
This study examines the provisions of additional criminal penalties in the form of replacement money in the corruption case of the former Regent of Kupang Regency, Ibrahim Agustinus Medah, based on Decision No. 78/Pid.Sus-TPK/2021/PN.KPG. Based on these problems, this study focuses on two main aspects, namely how to apply additional criminal penalties in the form of replacement money in corruption crimes in accordance with applicable law. This study uses an empirical legal research method with a regulatory-statutory approach and a conceptual approach. The results of the study show that although additional criminal penalties in the form of replacement money have been regulated in the Indonesian criminal law system, their implementation still faces various obstacles. Some of the main obstacles found in this study include the difficulty of the process of proving assets that can be confiscated, the limited financial ability of the convict to pay replacement money, the slow process of executing the verdict, and the lack of effective supervision in the implementation of this additional penalty. Therefore, improvements are needed in the execution mechanism, increased transparency in law enforcement, and strengthened supervision and coordination between related institutions to increase the effectiveness of the application of additional criminal penalties in corruption cases.